PROSTAGLANDIN-E2 AND LEUKOTRIENE-C4 LEVELS FOLLOWING DIFFERENT REPERFUSION PERIODS IN RAT-BRAIN CORRELATED WITH MORPHOLOGICAL-CHANGES - (:unkn) unknown (CHURCHILL LIVINGSTONE, 1992)
Prostaglandin E2 (PGE2) and leukotriene C4 (LTC4) are the metabolites of arachidonic acid (AA) that increase in forebrain following global ischemia and reperfusion. These mediators are highly potent vasoconstrictors of cerebral arteries leading to enhanced vascular permeability that induces the formation of vasogenic edema. In this study, after developing an experimental animal model simulating the concept of ischemic penumbra in the rat, the levels of PGE2 and LTC4 produced in the forebrain were measured and the effects of these mediators in short duration and prolonged reperfusion were investigated and then correlated with nueropathological findings. We found statistically significant reduction both in PGE2 and LTC4-like activities after just 10 min ischemia (p<0.05, p<0.05). PGE2-like activity significantly increased in the 4th and 60th min of reperfusion (p<0.05, p<0.05). In the 15th min of reperfusion, PGE2 was found to be significantly reduced (p<0.005) that may be due to the formation of free oxygen radicals by activation of PG hydroperoxidase reaction that inhibits PGE2 production in the cyclooxygenase pathway. LTs were not significantly increased in any reperfused group. Inhibition of the lipoxygenase pathway of AA metabolism may occur as a result of 15-HPETE (15-hydroperoxyeicosatetraenoic acid) production. Pathologically, edema and degeneration of brain tissue were seen beginning from the 4th min of reperfusion that reached a peak in the 60th min of reperfusion which is in accordance with biochemical changes in the damaged tissue. It is concluded that by preventing the formation of AA metabolites in the early hours of ischemia and reperfusion, it could be possible to increase blood now in the ischemic penumbra that should limit the infarct area.
Keywords: CEREBRAL BLOOD-FLOW; GUINEA-PIG; ISCHEMIA; GERBIL; INJURY; TISSUE; MODEL; EDEMA; ACID